GOING CONCERN DAN OPINI AUDIT (SUATU STUDI PADA PERUSAHAAN PERBANKAN DI BEI) (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to examine the effect of liquidity, profitability and solvency of the auditor in providing audit opinions with going concern. Based on the results of the analysis is known that proper regression model used for analysis.By using logistic regression test of this study concluded that: (1) Variables of liquidity in this study consisted of Quick Ratio (QR) and the Banking Ratio (BR). Variable Quick Ratio (QR) does not affect the going concern audit opinion. While liquidity is measured by using the Banking Ratio (BR) did not affect the going concern audit opinion. (2) profitability variables in this study consisted of Return On Assets (ROA) and Interest Margin Loan (IML). Variable Return On Assets (ROA) affect the going concern audit opinion. While profitability is measured using the Interest Margin Loan (IML) does not affect the going concern audit opinion. (3) solvency variables in this study consists of the Capital Ratio (CR) and Adequency Capital Ratio (CAR) does not affect the going concern audit opinion. Keywords: liquidity, profitability and solvency and going concern audit opinion